Ultra-high strength yet superplasticity in a hetero-grain-sized nanocrystalline Au nanowire. (28th February 2022) - Fu, Libo; Kong, Deli; Yang, Chengpeng; Teng, Jiao; Lu, Yan; Guo, Yizhong; Yang, Guo; Yan, Xin; Liu, Pan; Chen, Mingwei; Zhang, Ze; Wang, Lihua; et al.
Highlights: Nanocrystalline nanowire always exhibits strength-ductility trade-off. Here, we provide in situ atomic-scale evidence that hetero-grain-sized nanocrystalline nanowires are simultaneously ultra-strong and ductile, with no strength-ductility trade-off. The hetero-grain-sized nanocrystalline nanowire exhibits a super uniform elongation of ∼ 236% and high strength of ∼ 2.34 gigapascals at room temperature. The in situ atomic-scale observations revealed that the dislocation activities, grain boundary plasticity, and surface atoms diffusion all contribute to the super elongation ability of hetero-grain-sized nanocrystalline nanowire. Abstract: Nanocrystalline metals often display a high strength up to the gigapascal level, yet they suffer from poor plasticity. Previous studies have shown that the development of hetero-sized grains can efficiently overcome the strength-ductility trade-off of nanocrystalline metals. However, whether this strategy can lead to the fabrication of nanocrystalline nanowires exhibiting both high strength and superplasticity is unclear, similar to the atomistic deformation mechanism. In this paper, we show that ultra-small nanocrystalline Au nanowires comprising grains in both the Hall–Petch and inverse Hall–Petch grain-size regions can exhibit extremely high uniform elongation (236%) and high strength (2.34 gigapascals) at room temperature. In situ atomic-scale observations revealed that the plastic deformation underwent two stages. In the first stage, the super-elongation ability originated from the intergrain plasticity of small grains via mechanisms such as grain boundary migration and grain rotation. This intergrain plasticity caused the grains in the heterogeneous-structured nanowires to grow very large. In the second stage, the super-elongation ability originated from intragrain plasticity accompanied by the diffusion of surface atoms. Our results show that the hetero-grain-sized nanocrystalline nanowires, comprising grains with sizes both in the strongest Hall–Petch effect region and the inverse Hall–Petch effect region, were simultaneously ultra-strong and ductile. They displayed neither a strength-ductility trade-off nor plastic instability. Graphical abstract: Image, graphical abstract